2013
DOI: 10.5301/hipint.5000039
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Plasma D-Dimer Value for Predicting Deep Venous Thrombosis following Hip Arthroplasty with Nadroparin Prophylaxis

Abstract: The aim of the study was to assess the value of D-dimer as an event predicitor for deep vein thrombosis (DVT) in patients given low molecular weight heparin (LMWH) after total hip arthroplasty (THA). Plasma D-dimer levels were obtained preoperatively and at days 1, 3, and 7 postoperatively in 83 consecutive patients undergoing THA treated with nadroparin prophylaxis plus intermittent pneumatic compression. Unilateral ascending venography was performed at postoperative day 7 or 8. There was a significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated the association of inflammatory status with hypercoagulability status [ 13 , 14 ]. Moreover, various inflammatory biomarkers with predictive significance in the diagnosis of post-TKA DVT have been studied in the last ten years [ 15 , 16 , 17 ]. Interleukin-6 (IL-6) and C-reactive protein (CRP) are two of the most studied inflammatory biomarkers in the prediction of complications following TKA [ 18 , 19 , 20 , 21 ], but unfortunately, the results are inconsistent and unsatisfactory, with high sensitivity but low specificity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the association of inflammatory status with hypercoagulability status [ 13 , 14 ]. Moreover, various inflammatory biomarkers with predictive significance in the diagnosis of post-TKA DVT have been studied in the last ten years [ 15 , 16 , 17 ]. Interleukin-6 (IL-6) and C-reactive protein (CRP) are two of the most studied inflammatory biomarkers in the prediction of complications following TKA [ 18 , 19 , 20 , 21 ], but unfortunately, the results are inconsistent and unsatisfactory, with high sensitivity but low specificity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Venography and ultrasound are commonly used diagnostic techniques for DVT, which are inconvenient, costly, or invasive. Many studies have focused on the serology, trying to find valuable biomarkers of DVT such as D-dimer, P-selection, Factor VII, and so on [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…d -dimer, a predictive factor for VTE, is widely used in clinical practice as a diagnostic aid for suspected VTE. [27,28] In our study, the preoperative values of d -dimer were mostly in normal range, showed no significant differences in DVT group and non-DVT group. And the results of duplex ultrasonography, bilateral venography and CT pulmonary angiography preoperatively were negative.…”
Section: Discussionmentioning
confidence: 44%